Prehospital neurological deterioration in stroke. Issue 8 (27th April 2018) - Slavin, Sabreena J; Sucharew, Heidi; Alwell, Kathleen; Moomaw, Charles J; Woo, Daniel; Adeoye, Opeolu; Flaherty, Matthew L; Ferioli, Simona; McMullan, Jason; Mackey, Jason; De Los Rios La Rosa, Felipe; Martini, Sharyl; et al.
Abstract : Background and purpose: Patients with stroke can experience neurological deterioration in the prehospital setting. We evaluated patients with stroke to determine factors associated with prehospital neurological deterioration (PND). Methods: Among the Greater Cincinnati/Northern Kentucky region (population 1.3 million), we screened all 15 local hospitals' admissions from 2010 for acute stroke and included patients aged ≥20. The GCS was compared between emergency medical services (EMS) arrival and hospital arrival, with decrease ≥2 points considered PND. Data obtained retrospectively included demographics, medical history and medication use, stroke subtype (eg, ischaemic stroke (IS), intracerebral haemorrhage (ICH), subarachnoid haemorrhage (SAH)) and IS subtype (eg, small vessel, large vessel, cardioembolic), seizure at onset, time intervals between symptom onset, EMS arrival and hospital arrival, EMS level of training, and blood pressure and serum glucose on EMS arrival. Results: Of 2708 total patients who had a stroke, 1092 patients (median (IQR) age 74 (61–83) years; 56% women; 21% black) were analysed. PND occurred in 129 cases (12%), including 9% of IS, 24% of ICH and 16% of SAH. In multivariable analysis, black race, atrial fibrillation, haemorrhagic subtype and ALS level of transport were associated with PND. Conclusion: Haemorrhage and atrial fibrillation is associated with PND in stroke, and further investigation is needed to establish whether PND can be predicted. Further studies are also needed to assess whether preferential transport of patients with deterioration to hospitals equipped with higher levels of care is beneficial, identify why race is associated with deterioration and to test therapies targeting PND.